The potential for enhanced water decoupling in the Jordan Basin through regional agricultural best practice - Gilmont, M; Nassar, L; Rayner, S; Tal, N; Harper, E; Salem, H (MDPI, 2018)
This paper examines the differences in agricultural water application per crop ton output in the semi-arid, jurisdictions in the Jordan Basin, focusing on Israel and Jordan, with some analysis relevant to Palestine. It delivers a nationally averaged assessment of applied water application for 14 key regional crops, to understand differences in water application, with most cases suggesting Israeli best practice in water application per unit crop. The paper draws on secondary assessment of agricultural water intensity, and primary data from farmer interviews to demonstrate differences in applied water productivity and agricultural context. The analysis suggests a conservative estimate that a difference of 168MCM/yr (33% or agriculture and 18% national total) exists in terms of water application for a given crop production in Jordan compared to Israel. The paper then proposes further work required to establish how differences in water application might translate into differences in agricultural water productivity, and thereby potential water savings that might enable growth of production within current agricultural allocations, allowing future new resources to be allocated to other economic and social needs. The paper also delivers a preliminary analyses the political and institutional landscape for implementation, assessing the challenges of institutional silos and overlap that some policy stakeholders see as hindering cross-sectoral progress. The paper concludes by examining the limitations of the analysis, and proposes future work to deepen the robustness of results, and examines some of the challenges facing improved agricultural water productivity and changing farm behaviour in the region.